Impact of the pandemic on the improvement of the electoral system and electoral legislation of the Republic of Kazakhstan in view of the elections held - Ibrayeva, N.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article discusses the current problems of improving the electoral system in the Republic of Kazakhstan in the context of a pandemic. It gives a brief description of the past elections of deputies of the Majilis of the Parliament and deputies of the maslikhat of the Republic of Kazakhstan. The article presents a legal assessment of the normative legal acts regulating issues in the field of elections, including an analysis of the Resolution of the Central Election Commission of the Republic of Kazakhstan dated December 4, 2020, on election procedure. A brief analysis of the Constitutional Law of the Republic of Kazakhstan «On elections in the Republic of Kazakhstan» in terms of the amendments made regarding the direct election of akims of cities of districtsignificance, rural districts, towns, and villages. In addition, the resolution of the European Parliament adopted on the results of the election campaigns and the recommendations specified in it are being considered. The author offers her vision on the issues of election campaigning, analyzing the experience of other foreign countries. The article provides examples of international experience on the issues of campaigning by candidates and political parties. The necessary proposals are given to improve the institution of elections in general and the development of a multiparty system as one of the conditions in building a developed, competitive state with an effective electoral system. In this connection, based on the study of monographic studies and normative legal acts, specific proposals were put forward to improve the electoral legislation and the electoral system as a whole, in the conditions of a pandemic.